Peran Perawat dalam Pelaksanaan Senam Hipertensi pada Lansia di Panti Tresna Werdha Budi Mulia I Cipayung - Aliana Dewi; Ulfah Nuraini Karim; Sondang Manurung; Erika Lubis (JURNAL ABDIMAS SERAWAI, 2024)
Hypertension is the most common cardiovascular disease in adults and the elderly. Regular exercise at a moderate level for three days per week for 30 minutes/day. Regular aerobic exercise causes a decrease in systolic and diastolic blood pressure by 11 and 8 mmHg. The purpose of this community service is to provide an understanding of the importance of the Role of Nurses in the Implementation of Hypertension Gymnastics in the elderly at the Panti Tresna Werdha Budi Mulia I Cipayung and with the presence of Hypertension Gymnastics in implementing preventive efforts in the form of counseling on hypertension, socialization and education. In implementing this community service activity, the author carried out a Professional Guidance Practice program with the aim of providing nursing care and learning in community service carried out outside the campus. The methods used were blood pressure examinations and health counseling and Demonstration. The results of this service showed that significant changes in blood pressure with the provision of elderly gymnastics were able to reduce blood pressure by an average of 10 mmHg. From the results of the activity, it is recommended that nurses be more continuous in carrying out hypertension gymnastics activities and continuous monitoring and evaluation